Housing tenure as a focus for reducing inequalities in the home safety environment: evidence from Growing Up in New Zealand. (27th July 2017) - Berry, Sarah; Carr, Polly Atatoa; Kool, Bridget; Mohal, Jatender; Morton, Susan; Grant, Cameron
Abstract: Objectives: To determine whether specific demographic characteristics are associated with the presence or absence of household safety strategies. Methods : This study was conducted within Growing Up in New Zealand, a contemporary longitudinal study of New Zealand (NZ) children. Multivariable analyses were used to examine the maternal (self‐prioritised ethnicity, education, age, self‐reported health) and household (area‐level deprivation, tenure, crowding, residential mobility, dwelling type) determinants of household safety strategies being present in the homes of young children. Results : In comparison to family‐owned homes, privately owned rental homes were less likely (OR=0.78; 95%CI 0.65–0.92), and government‐owned rental homes were more likely (OR=1.74, 95%CI 1.25–2.41) to have eight or more household safety strategies present. Conclusions : Living in a privately owned rental home in NZ exposes children to an environment where there are fewer household safety strategies in place. Implications for public health : Housing tenure provides a clear target focus for improving the household safety environment for NZ children.